Penyelesaian Sengketa Ekonomi Syariah Melalui Badan Arbitrase Syariah Nasional(Studi Kasus Basyarnas Yogyakarta) - Permana, Rajib, Mutimatun Ni'ami, S.H., M.Hum (2017)
This study outlined legal standing of arbitration in the judicial system of Indonesia. It aimed whether any legal attempt is allowed by the law towards the court's award in accordance with the law principle of award "final and binding". legal-normative research method was used by the author with an analytical of qualitative description. As the result showed that arbitration is an extra judicial organization based on International Law which had been ratiied by the government to compliment the judicial system in Indonesia. And no legal attempt is allowed to the "inal and binding" One of the advantages of settlement through arbitration in comparison to court, the parties are free to determine which procedural law to be applied. In addition, in Indonesia there are national arbitration also a Sharia arbitration. The objective in this research is the first to examine the dispute settlement procedures of syariah economicthrough Basyarnas.